Spatiotemporal Analysis of Drought Characteristics in Song-Liao River Basin in China - Xiaojing Shen; Xu Wu; Xinmin Xie; Zhenzhen Ma; Meijian Yang (Advances in Meteorology)
The monthly accumulated precipitation and monthly average temperature of 117 meteorological stations in Song-Liao River Basin (SLRB) were used to calculate the Standardized Precipitation Evapotranspiration Indices (SPEI) to analyze the drought characteristics, including long-term trends, drought affected area, climate abrupt change, intensive drought occurrence regions, and drought durations during 1964–2013 with the support of GIS. The Area Drought Severity (ADS), a comprehensive index, is proposed to assess both the variations of drought degree and the extent of the drought affected area. The results revealed that (1) the drought happening probability and degree are rising and the affected areas of all degrees of drought have an increasing trend during the last 50 years; (2) there is a climate abrupt change which occurred in around 1994, and the area with declining SPEI is larger than that with declining SPI, which could be due to the rising temperature after the climate abrupt change; (3) all degrees of drought occurrence probability increased, and the intensive drought occurrence regions altered from the northern SLRB to the southwestern SLRB after the climate abrupt change; (4) the drought duration increased from 1994, and the increased drought durations occurred in most parts of SLRB.